Coexistence of composite bosons and composite fermions in nu = 1/2 + 1/2 quantum Hall bilayers. - Simon, S; Rezayi, E; Milovanovic, M (2003)
In bilayer quantum Hall systems at filling fractions near nu=1/2+1/2, as the spacing d between the layers is continuously decreased, intralayer correlations must be replaced by interlayer correlations, and the composite fermion (CF) Fermi seas at large d must eventually be replaced by a composite boson (CB) condensate or "111 state" at small d. We propose a scenario where CBs and CFs coexist in two interpenetrating fluids in the transition. Trial wave functions describing these mixed CB-CF states compare very favorably with exact diagonalization results. A Chern-Simons transport theory is constructed that is compatible with experiment.